TRAINING FUTURE SPECIAL TEACHERS FOR PROFESSIONAL ACTIVITIES - Sharofat Nurullaevna Ibadullayeva (Web of Journals Publishing, 2024)
The article examines the issues of improving the system of training teachers in the conditions of the new Uzbekistan using innovative models. The reforms in the education system, the introduction of personality-oriented learning, the organization of pedagogical practice, as well as the activities of professional clubs, such as "Pedagogical Desantura" are analyzed. Particular attention is paid to the formation of professional skills of students and the introduction of innovative approaches to the educational process. The importance of the cluster approach and transformational activities in the training of teachers is emphasized. Key words: innovative models, student-centered learning, pedagogical practice, “Pedagogical landing force”, cluster approach, training of teaching staff, transformational activities.